Networking with a purpose: men and women's perception of career networking in sport NGBs. Issue 3 (10th July 2017) - Zdroik, Jen; Babiak, Kathy
Abstract : Purpose: Networking practices are considered to be an important career advancement strategy. However, little empirical research exists which provides understanding of this phenomenon as it relates to the differences in practices and experiences between genders. The purpose of this paper is to explore how the role and nature of networking and career relationships in nonprofit sport organizations is perceived to impact career development. Design/methodology/approach: In total, 34 semi-structured interviews were conducted with male and female executives in a range of nonprofit organizations to elicit views, attitudes, and information regarding formal and informal networking strategies and practices employed in this context. Findings: Findings highlight differences in perceptions of how networking is defined, the central role of mentors, the nature of networking relationships, and networking strategies. The authors found that there are various perceived barriers with regard to gender and organizational culture in sport national governing bodies (NGBs). Research limitations/implications: Networking practice and policy implications are discussed for sport NGBs and other organizations. The authors offer recommendations for future research. Originality/value: The project adds value to the understanding of the career advancement of women as it directly compares perceptions of men and women.